The monad induced by the hom-functor in the category of topological spaces and its associated Eilenberg-Moore algebras - Koena R. Nailana (International Journal of Mathematics and Mathematical Sciences)
We discuss the monad associated with the topology of pointwise convergence. We also study examples of the Eilenberg-Moore algebras for this monad.